Grounded Theory as a “Family of Methods”: A Genealogical Analysis to Guide Research - Wayne A. Babchuk (Adult Education Research Conference, 2010)
This inquiry traces the evolution of grounded theory from a nuclear to an extended family of methods and considers the implications that decisionmaking based on informed choices throughout all phases of the research process has for realizing the potential of grounded theory for advancing adult education theory and practice.